Fast sliding mode control on air-breathing hypersonic vehicles with transient response analysis. (January 2016) - Mu, Chaoxu; Sun, Changyin; Xu, Wei
This article studies the tracking control of air-breathing hypersonic vehicles to the reference velocity and the reference altitude with a fast non-linear sliding mode control scheme. By the feedback linearization technology, the longitudinal model of air-breathing hypersonic vehicles is divided into the velocity subsystem and the altitude subsystem. Two lumped tracking error variables are developed based on velocity and altitude subsystems, and non-singular terminal sliding mode control is used so that the two lumped error variables converge to the origin in finite time. During the tracking process, transient properties of non-singular terminal sliding mode control are investigated from the mathematical and theoretical standpoint. The simulation results have shown that the fast non-linear sliding mode control is effective for the tracking control of air-breathing hypersonic vehicles and have demonstrated that the relevant transient response analysis is correct.